(untitled) (Research, Society and Development, 2021)
The amazon genus comprises parrots which are among the most popular birds as pets, precisely because of their docile habit and ability to reproduce sounds. They have zygodactyl feet, curved and developed beak, which give the ability to climb trees and ability to handle food. This project aimed to describe the anatomy of the lumbosacral plexus of 10 (ten) specimens of mangrove parrot (Amazona amazonica) donated to the Veterinary Anatomy Laboratory of the Federal University of Campina Grande by CETAS / IBAMA-PB. The animals were fixed and preserved in 10% formaldehyde solution and the lumbosacral plexus nerves were subsequently dissected. The lumbar plexus is formed by the roots of the lumbar nerves 1, 2 and 3; the sacral plexus is formed by the roots of the sacral nerves 1, 2, 3, 4 and 5 and the pudendal plexus has 4 origins from the sacral segments of the spinal cord. The lumbar plexus after branching forms two main nerves, the lateral femoral cutaneous and the cranial femoral cutaneous. From the sacral plexus arises the sciatic nerve, from which four branches originate: tibial nerve, common fibular nerve, caudal femoral cutaneous nerve and thigh caudal nerve. The sciatic nerve innervates all the musculature that act on the knee and finger joints. In general the origin and branches of the lumbosacral plexus are similar in poultry.